Carbonate and silicate biomineralization in a hypersaline microbial mat (Mesaieed sabkha, Qatar): Roles of bacteria, extracellular polymeric substances and viruses. Issue 4 (7th December 2017) - Perri, Edoardo; Tucker, Maurice E.; Słowakiewicz, Mirosław; Whitaker, Fiona; Bowen, Leon; Perrotta, Ida D.
Abstract: In a modern peritidal microbial mat from Qatar, both biomediated carbonates and Mg‐rich clay minerals (palygorskite) were identified. The mat, ca 5 cm thick, shows a clear lamination reflecting different microbial communities. The initial precipitates within the top millimetres of the mat are composed of Ca–Mg–Si–Al–S amorphous nanoparticles (few tens of nanometres) that replace the ultrastructure of extracellular polymeric substances. The extracellular polymeric substances are enriched in the same cations and act as a substrate for mineral nucleation. Successively, crystallites of palygorskite fibres associated with carbonate nanocrystals develop, commonly surrounding bacterial bodies. Micron‐sized crystals of low‐Mg calcite are the most common precipitates, together with subordinate aragonite, very high‐Mg calcite/dolomite and ankerite. Pyrite nanocrystals and framboids are present in the deeper layers of the mat. Calcite crystallites form conical structures, circular to triangular/hexagonal in cross‐section, evolving to crystals with rhombohedral terminations; some crystallite bundles develop into dumb‐bell and stellate forms. Spheroidal organo‐mineral structures are also common within the mat. Nanospheres, a few tens of nanometres in diameter, occur attached to coccoid bacteria and within their cells; these are interpreted as permineralized viruses and could be significant as nuclei for crystallite‐crystal precipitation. Microspheres, 1 to 10 μm in diameter, result from intracellular permineralization within bacteria or the mineralization of the bacteria themselves. Carbonates and clay minerals are commonly aggregated to form peloids, tens of microns in size, surrounded by residual organic matter. Magnesium silicate and carbonate precipitation are likely to have been driven by pH – saturation index – redox changes within the mat, related to microenvironmental chemical changes induced by the microbes – extracellular polymeric substances – viruses and their degradation.